Development of harmonised food and sample lists for total diet studies in five European countries. Issue 6 (2nd June 2016) - Dofkova, Marcela; Nurmi, Tanja; Berg, Katharina; Reykdal, Ólafur; Gunnlaugsdóttir, Helga; Vasco, Elsa; Dias, Maria Graça; Blahova, Jitka; Rehurkova, Irena; Putkonen, Tiina; Ritvanen, Tiina; Lindtner, Oliver; et al.
ABSTRACT: A total diet study (TDS) is a public health tool for determination of population dietary exposure to chemicals across the entire diet. TDSs have been performed in several countries but the comparability of data produced is limited. Harmonisation of the TDS methodology is therefore desirable and the development of comparable TDS food lists is considered essential to achieve the consistency between countries. The aim of this study is to develop and test the feasibility of a method for establishing harmonised TDS food and sample lists in five European countries with different consumption patterns (Czech Republic, Finland, Germany, Iceland and Portugal). The food lists were intended to be applicable for exposure assessment of wide range of chemical substances in adults (18–64 years) and the elderly (65–74 years). Food consumption data from recent dietary surveys measured on individuals served as the basis for this work. Since the national data from these five countries were not comparable, all foods were linked to the EFSA FoodEx2 classification and description system. The selection of foods for TDS was based on the weight of food consumed and was carried out separately for each FoodEx2 level 1 food group. Individual food approach was respected as much as possible when the TDS samples were defined. TDS food lists developed with this approach represented 94.7–98.7% of the national total diet weights. The overall number of TDS samples varied from 128 in Finland to 246 in Germany. The suggested method was successfully implemented in all five countries. Mapping of data to the EFSA FoodEx2 coding system was recognised as a crucial step in harmonisation of the developed TDS food lists.